2023
DOI: 10.1111/ejn.16085
|View full text |Cite
|
Sign up to set email alerts
|

The performance of plasma phosphorylated tau231 in detecting Alzheimer's disease: A systematic review with meta‐analysis

Abstract: Cerebrospinal fluid (CSF) phosphorylated tau231 (P‐tau231) is associated with neuropathological outcomes of Alzheimer's disease (AD). The invasive access of cerebrospinal fluid has greatly stimulated interest in the identification of blood‐based P‐tau231, and the recent advent of single‐molecule array assay for the quantification of plasma P‐tau231 may provide a turning point to evaluate the usefulness of P‐tau231 as an AD‐related biomarker. Yet, in the plasma P‐tau231 literature, findings with regard to its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Other recent studies also show that plasma p-Tau231 can identify AD patients with other non-AD neurodegenerative diseases [56] and that abnormal levels of plasma p-Tau231 are reached in preclinical AD stages [57]. A recent systematic review reported that plasma p-Tau231 increased from CU to MCI to AD and showed an excellent diagnostic accuracy for asymptomatic Aβ pathology [58].…”
Section: Blood-based Total Tau and Phosphorylated Taumentioning
confidence: 96%
“…Other recent studies also show that plasma p-Tau231 can identify AD patients with other non-AD neurodegenerative diseases [56] and that abnormal levels of plasma p-Tau231 are reached in preclinical AD stages [57]. A recent systematic review reported that plasma p-Tau231 increased from CU to MCI to AD and showed an excellent diagnostic accuracy for asymptomatic Aβ pathology [58].…”
Section: Blood-based Total Tau and Phosphorylated Taumentioning
confidence: 96%